2022
DOI: 10.1021/jacs.2c02487
|View full text |Cite
|
Sign up to set email alerts
|

Switchable 1,2-Rearrangement Enables Expedient Synthesis of Structurally Diverse Fluorine-Containing Scaffolds

Abstract: Skeletal rearrangement that changes the connectivity of the molecule via cleavage and reorganization of carbon–carbon bonds is a fundamental and powerful strategy in complex molecular assembly. Because of the lack of effective methods to control the migratory tendency of different groups, achieving switchable selectivity in skeletal rearrangement has been a long-standing quest. Metal-based dyotropic rearrangement provides a unique opportunity to address this challenge. However, switchable dyotropic rearrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 91 publications
0
25
0
Order By: Relevance
“…We initiated our study by evaluating the three-component coupling reaction of (3-(trifluoromethyl)­but-3-en-1-yn-1-yl)­benzene ( 1 ), cyclohexane ( 2 ), and ethyl 4-bromobenzoate ( 3 ) in the presence of TBADT, Ni­(COD) 2 , bipyridine, and K 3 PO 4 under near-ultraviolet light [10 W light-emitting diodes (LEDs)] irradiation (Table ). As expected, gem -difluoroalkene 5 formed by radical addition/fluoride elimination is the main product of the reaction (30%), while the yield of the desired CF 3 -allene product 4 is only 8% (Table , entry 1). A series of ligands ( L2 – L5 ) were screened (entries 2–5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We initiated our study by evaluating the three-component coupling reaction of (3-(trifluoromethyl)­but-3-en-1-yn-1-yl)­benzene ( 1 ), cyclohexane ( 2 ), and ethyl 4-bromobenzoate ( 3 ) in the presence of TBADT, Ni­(COD) 2 , bipyridine, and K 3 PO 4 under near-ultraviolet light [10 W light-emitting diodes (LEDs)] irradiation (Table ). As expected, gem -difluoroalkene 5 formed by radical addition/fluoride elimination is the main product of the reaction (30%), while the yield of the desired CF 3 -allene product 4 is only 8% (Table , entry 1). A series of ligands ( L2 – L5 ) were screened (entries 2–5).…”
Section: Resultsmentioning
confidence: 99%
“…(1) β-F elimination is a facile event . The previously reported radical addition reactions of 2-trifluoromethyl-1,3-enynes only produced gem -difluoroalkenes . (2) The direct arylation of Csp 3 –H bonds is difficult to avoid .…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the great progress recorded in the field of transition-metal-catalyzed C–H and C–C bond activation, dual functionalization of α- and β-carbons of saturated carbonyl compounds remains an unknown synthetic transformation in spite of its synthetic significance. We have recently reported a 1,2-aryl­(alkyl)/Pd­(IV) dyotropic rearrangement, while Kong and co-workers described a Ni­(I)-based counterpart . On the basis of these observations, we speculated that it might be possible to accomplish this task in one operation if the in situ formed β-C–Pd species could undergo a 1,2-positional interchange with one of the substituents of the α-quaternary carbon. Our working hypothesis is outlined in Scheme c.…”
mentioning
confidence: 96%
“…While the role of the combination of phosphine and nitrogen ligands is unclear, the presence of PCy 3 improved both the yield and ee value of 3a (entries 1–3) . The group of Kong has recently isolated a related tridentate N 3 -coordinated cyclized alkyl–Ni­(II)­LBr intermediate, which is tetracoordinated, very unstable, and can be rapidly decomposed to alkyl–H. We consider that PCy 3 may have a coordinative interaction with Ni­(II) to stabilize such an intermediate, and we observed that it significantly inhibited the formation of cyclization–protonation byproducts.…”
mentioning
confidence: 99%
“…On the basis of these results and previous reports, we tentatively propose a catalytic cycle for this transformation as shown in Scheme . The reaction of oxime ester with Ni(0) affords complex A , which undergoes an enantioselective migratory insertion into alkene to afford cyclized intermediate B . ,, The combination of this Ni­(II) species with an alkyl radical, followed by reductive elimination, gives the desired product 3 and Ni­(I). , Alkyl radical can be generated by the reaction of alkyl iodide with Ni­(I) species. , …”
mentioning
confidence: 99%